2004
DOI: 10.1093/jnci/djh252
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Flow Cytometric Analysis of Inter-Patient Variation in STAT1 Phosphorylation Following Interferon Alfa Immunotherapy

Abstract: This flow cytometry method can be used to monitor STAT1 activation within subsets of immune cells from patients undergoing IFN alpha immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 30 publications
5
70
0
Order By: Relevance
“…5E). As had been noted in previous studies, each patient exhibited a unique dose-response curve for IFN-a -induced P-STAT1 in PBMCs (22). A paired sample t test revealed that mean levels of P-STAT1 were significantly higher in patient PBMCs following stimulation with 10 3 and 10 4 units/mL IFN-a (P = 0.046 and 0.038, respectively; n = 6) than in the corresponding tumor cells.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…5E). As had been noted in previous studies, each patient exhibited a unique dose-response curve for IFN-a -induced P-STAT1 in PBMCs (22). A paired sample t test revealed that mean levels of P-STAT1 were significantly higher in patient PBMCs following stimulation with 10 3 and 10 4 units/mL IFN-a (P = 0.046 and 0.038, respectively; n = 6) than in the corresponding tumor cells.…”
Section: Resultssupporting
confidence: 69%
“…Total levels of intracellular STAT1, STAT2, and Tyr 701 P-STAT1 were measured by flow cytometry as described previously (22). Data were expressed as specific fluorescence (Fsp = Ft -Fb), where Ft represents the median value of total staining and Fb represents the median value of background staining with an isotype control antibody (22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly found dysfunction of NK cells in breast cancer patients [120][121][122] is probably the consequence of cytokine dysbalance due to the prevalence of immunosuppressive cytokines such as IL-10 and TGF [123], as well as tumor-produced inhibitory factors [124]. This finding is in concordance with the only previous study published for breast cancer patients [125] and also with several other investigations showing STAT dysregulation in PBL of melanoma and renal cell carcinoma patients [126,127]. Moreover, we showed that breast cancer patients' T and NK cell subsets have lower pSTAT1 level that could be a biomarker of decreased NK cell cytotoxicity and IFN production associated with progression of this disease [120,128,129].…”
Section: Stat Dysfunction Associated With Different Malignanciessupporting
confidence: 87%
“…In fact, recent data have shown that the occurrence of autoimmune sequelae and the presence of tumor-infiltrating lymphocytes correlate with clinical response in patients receiving IFN-a (23,24). Our previous analysis of IFN-a -induced JAK-STAT signal transduction in immune cells revealed reduced phosphorylation of these proteins at higher doses of IFN-a (25). We therefore hypothesized that intermediate and high doses of IFN-a might be equally effective in activating STAT proteins and inducing the expression of ISGs in patient peripheral blood mononuclear cells (PBMC).…”
mentioning
confidence: 93%